Back Cover: Sensitivity enhancing injection from a sample reservoir and channel interface in microchip electrophoresis. Issue 4 (February 2017) - Wuethrich, Alain; Quirino, Joselito P.
Abstract : J. Sep. Sci . 2017, 40, 927–932 DOI:10.1002/jssc.201601064 The Back Cover picture shows a stacking injection for microchip electrophoresis. The cationic analyte is stacked via micelle to solvent stacking at the boundary of the sample reservoir and channel. The micelle‐bound analyte is carried to the boundary where the presence of organic solvent causes a release from the micelles and analyte stacking at the channel interface. After stacking, the analyte is injected into the channel by reversing the voltage. This simple injection strategy yielded a 150‐fold sensitivity improvement.